Estimating the roles of dependency ratio and economic growth on child mortality in SAARC countries: Evidence from panel data analysis - Cheema, Ahmed Raza; Cheema, Abdullah; Cheema, Amna; Ul-Haq, Jabbar; Visas, Hubert (Edelweiss Applied Science and Technology, 2023)
In developing nations like the SAARC, child mortality is an issue. The health status of an economy can be effectively assessed through its significant indicators. In situations where mortality rates are elevated, there is a corresponding increase in the fertility rate as parents seek to compensate for the higher likelihood of child mortality. This leads to a decrease in the allocation of resources per child in terms of education and healthcare, inadvertently hindering the development of human capital and perpetuating the cycle of poverty and illness. National GDP is lowered by high death rates. This study estimates the roles of dependency ratio and economic growth on child mortality using cross-country data for SAARC countries. The study applies panel data techniques (Fixed Effect Model, Random Effect Model, Generalized Least Square Regression, and Panel Corrected Standard Error regression). Based on the Hausman Specification Test, the preferred model is Random effect model. In the case of heteroscedasticity, the better choice is GLS regression, especially when T is greater than cross-sections N. However, the study also estimates panel-corrected standard error regression. The findings reveal that there is a positive relationship between child mortality and the dependency ratio and a negative one between child mortality and economic growth. The study additionally evaluates the cumulative impacts of both variables on it. The findings indicate that the impact of both variables remains consistent. The policy implications are that economic growth-maximizing and dependency ratio-minimizing policies should be adopted. The study contributes to the existing literature by finding the role of dependency ratio in child mortality, at least with respect to SAARC countries.